2018
DOI: 10.3390/jmse6040139
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitivity Analysis of the Wind Forcing Effect on the Accuracy of Large-Wave Hindcasting

Abstract: Deployment of wave energy converters (WECs) relies on consistent and accurate wave resource characterization, which is typically achieved through numerical modeling using deterministic wave models. The accurate predictions of large-wave events are critical to the success of wave resource characterization because of the risk on WEC installation, maintenance, and damage caused by extreme sea states. Because wind forcing is the primary driver of wave models, the quality of wind data plays an important role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Though these differences are minor, the total energy is proportional to the square of the wave height. Thus, these minor differences are essential to capture as they can lead to dramatically different forecasts, affecting not only wave energy estimates, but also forecasts of hurricane-induced waves [35][36][37] and storm surges [38,39]. Consequently, the joint EMD-LSTM model displays a dramatically lower RMSE for wave forecasts compared to LSTM alone and thus, wherever possible, should be used.…”
Section: Resultsmentioning
confidence: 99%
“…Though these differences are minor, the total energy is proportional to the square of the wave height. Thus, these minor differences are essential to capture as they can lead to dramatically different forecasts, affecting not only wave energy estimates, but also forecasts of hurricane-induced waves [35][36][37] and storm surges [38,39]. Consequently, the joint EMD-LSTM model displays a dramatically lower RMSE for wave forecasts compared to LSTM alone and thus, wherever possible, should be used.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate wind forcing is extremely important for the wave hindcast. Wang et al [11] evaluated several wind products, and concluded that the Climate Forecast System Reanalysis (CFSR) provided the best overall performance in predicting wave heights using either WWIII or UnSWAN. The CFSR wind data are available from to 2010 at hourly temporal and 0.5-degree spatial resolution.…”
Section: B Model Configurationsmentioning
confidence: 99%
“…These models, however, underpredict large waves and extreme n-year significant wave heights. The main source of this underbias is due to limitations of most wind reanalysis datasets, namely their inability to resolve fine-scale high-energy wind gusts, e.g., [22,23]. Model performance studies commonly emphasize predictions of common sea state statistics (bulk parameters) on average, e.g., H s and peak period, T p .…”
Section: Introductionmentioning
confidence: 99%